Synthesis and swelling behaviour of hydrophobically modified responsive polymers in dilute aqueous solutions - Iyer, N. P.; Hourdet, Dominique; Badiger, Manohar V.; Chassenieux, Christophe; Perrin, P.; Wadgaonkar, P. (Polymer, 2005)
New series of associating polymers were synthesised in order to investigate opposite behaviours of hydrophobically modified water-soluble polymers and thermoresponsive water-soluble polymers carrying LCST stickers. On the basis of a poly(acrylic acid) backbone, amino-terminated poly(N-isopropylacrylamide), poly(ethylene oxide-co-propylene oxide) and/or dodecyl chains were grafted following a reaction of condensation activated by carbodiimide. Two homologous series of well-defined single grafted and double grafted copolymers were obtained, with double grafted chains containing both C12 and LCST grafts. The dilute solution properties of these copolymers were carefully studied by capillary viscometry. At low salt concentration and below the LCST of the grafts, the swelling properties of macromolecular chains are controlled either by intramolecular associations between hydrophobes, excluded volume effect exerted by hydrophilic grafts or by a balance between these opposite interactions. The deswelling of macromolecular chains, induced by hydrophobic interactions, is amplified at higher ionic strength and more particularly above the transition temperature of the side chains. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: associating polymers; poly(acrylic acid); viscometry

Synthesis and characterization of novel hydrophobically end-capped poly(ethylene oxide)s [PEOs] - Badiger, Manohar V.; Kadam, Vijay S.; Lele, Ashish K.; Wadgaonkar, P. P.; Hourdet, Dominique (Macromolecular Symposia, 2006)
We report on the synthesis and characterization of a novel hydrophobically modified end-capped poly(ethylene oxide)s. The end-capping agent of this polymer was designed and synthesised from a renewable resource material namely, gallic acid (i.e. 3,4,5-trihydroxybenzoic acid), the byproduct of tannin industry. The hydroxyl groups at 3, 4 and 5 positions of gallic acid provide an opportunity for varying the hydrophobicity of the compound. The hydrophobic end-capping compound, 3,4,5tridodecyloxy bezoylazide was prepared from gallic acid and PEGS with different chain lengths (of number average molecular weights, 10000 and 35000 g/mol) were endcapped. using 3,4,5-tridodecyloxybenzoyl azide. The quantitative analysis of end-capping in the polymers was demonstrated by H-1-NMR spectroscopy and the rheological studies were carried out in the surfactant solutions.
Keywords: end-capped PEOs; hydrophobically modified polymers; water-soluble polymers

Synthesis and self-assembling properties of alpha,omega-hydroxy-poly(ethylene oxide) end-capped with 1-isocyanato-3-pentadecylcyclohexane - Kadam, Vijay S.; Badiger, Manohar V.; Wadgaonkar, Prakash P.; Ducouret, Guylaine; Hourdet, Dominique (Polymer, 2008)
A novel hydrophobic compound, 1-isocyanato-3-pentadecylcyclohexane (PDC) issued from a renewable resource material (Cashew Nut Shell Liquid), is used to end-cap poly(ethylene oxide) (PEO) of different molecular weights. The synthesis, characterization and self-assembling properties of these new associating polymers are reported. In aqueous solution, PDC modified PEOs self-associate into micellar structures which are characterized by neutron scattering. Using a star-polymer model with sticky hard sphere interactions, it is shown that the characteristics of the micelles mainly depend on the size of the PEO chain. In the case of PDC stickers, the aggregation number decreases from 25 to 17 with increasing molecular weight of PEO, from 10 to 20 kg/mol, respectively. The temperature directly impacts the interaction potential between the hydrophilic coronas of PEO which become less repulsive with increasing temperature. Rheological measurements, performed in dilute solution, clearly demonstrate that PEO micelles self-associate into open supramolecular structures. The correlation length of these loose clusters increases with polymer concentration and the hierarchical self-assembly follows the rules of the percolation theory. The sol/gel transition takes place at the overlap concentration of clusters. In semi-dilute solution, the viscoelastic properties of PDC end-capped PEOs are well described by the Maxwell model with a single relaxation mode. The characteristic time of the network follows an Arrhenius temperature dependence with an activation energy of 70 kJ/mol, in very good agreement with the size of PDC stickers. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Associating polymer; Hydrophobically end-capped; poly(ethylene oxide); Star micelles

Synthesis and characterization of PEPO grafted carboxymethyl guar and carboxymethyl tamarind as new thermo-associating polymers - Gupta, Nivika R.; Torris, Arun A. T.; Wadgaonkar, Prakash P.; Rajamohanan, P. R.; Ducouret, Guylaine; Hourdet, Dominique; Creton, Costantino; Badiger, Manohar V. (Carbohydrate Polymers, 2015)
New thermo associating polymers were designed and synthesized by grafting amino terminated poly(ethylene oxide-co-propylene oxide) (PEPO) onto carboxymethyl guar (CMG) and carboxymethyl tamarind (CMT). The grafting was performed by coupling reaction between-NH2 groups of PEPO and -COOH groups of CMG and CMT using water-soluble EDC/NHS as coupling agents. The grafting efficiency and the temperature of thermo-association, T-assoc in the copolymer were studied by NMR spectroscopy. The graft copolymers, CMG-g-PEPO and CMT-g-PEPO exhibited interesting thermo-associating behavior which was evidenced by the detailed rheological and fluorescence measurements. The visco-elastic properties (storage modulus, G'; loss modulus, G'') of the copolymer solutions were investigated using oscillatory shear experiments. The influence of salt and surfactant on the T-assoc was also studied by rheology, where the phenomenon of ``Salting out'' and ``Salting in'' was observed for salt and surfactant, respectively, which can give an easy access to tunable properties of these copolymers. These thermo-associating polymers with biodegradable nature of CMG and CMT can have potential applications as smart injectables in controlled release technology and as thickeners in cosmetics and pharmaceutical formulations. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Carboxymethyl tamarind; Pluronics; Rheology; Solution behavior; Thermo-associating polymers